Eindexamencatalogus Academie Beeldende Kunsten Maastricht 96-97. - van Dijk, Paul (Maastricht : Academie Beeldende Kunsten, 1997)
Boese, Pedro ; Bahr, Oliver ; Brandts, Marianne ; Bisscheroux, Monique ; Camps, Barry ; Camps, Monique ; Frank, Tamar ; Emmerich, Hadassah ; Groen, Renate M. ; Engels, Heike ; Reeders, Miriam ; Schoener, Goerg ; van Wel, Daan ; Stienen, J. ; Yerna, Nico ; Vvedenskaie, Anna ; van Hoof, Yuri ; van den Bosch, Bert ; Lemmen, Annabelle ; Draaijer, Evelyne ; Verheijen, Ruben ; Roderburg, Kris ; Thomassen, Hugo ; Rosenzweig, Ron ; Technau, Serge ; Brouwers, Didier ; Bijvelde, E.M.A.M. ; Caris, Joop ; Boumans, Dittmar ; Diederen, Suzanne ; van den Eijnden, Mark ; Gorissen, Doortje ; Encina, Claudio ; Grimme, Uta ; Engels, Linda ; Guthan, Kaire ; Janssen, Mark ; Popma, Jesper ; Louwers, Tanja ; Schlechtriem, Bert ; Neven, Vincent ; Schmetz, Iva ; Steenbakkers, Meine ; Verpaalen, Nanda ; Stoffels, Esmeralda ; Torremans, Leon ; Gropoz, Emil ; Bertjens, Truus ; Gaude, Christina ; Bontje, Anna ; van der Gulik, Marianne ; Habets, Danielle ; Schumacher, Claudia ; Borghans, Edwin ; Schulkes-Derks, Doret ; van Elk, Marjon ; Prange, Jean ; Esther, Thomas ; Smedts, Judith ; Hart, Remy ; Syben, Oliver ; Verbraak, Pieter ; Witjes, Wies ; Weites, Wil ; Wiegersma, Foppe-Jan ; Borghouts, Bouk ; de Beer, Marlien ; Goossens, Esther Ina Marcella ; van den Berg, Pieter ; van der Grijn, Silvie ; Häuptli-Fumagli, Simone ; Hupperich, Nicola ; Hermens, Laura ; Kolkman, Floor ; Hol, Gonique ; van der Lubben, Claudia ; Merx, Linda ; Sterken, Caroline ; Oberendorff, Medy ; Syben, Nicole ; Spronken, Danny ; Veugen, Chantal ; van Wegberg, Bas ; Zmrzly, Dirk ; van den Berk, Ilse ; Brinke, Christa ten ; Gerritsen, Femke ; Kleeman, Christian ; van Gestel, Elouise ; Plum, Dirk ; Groeneveld, Bianca ; Rusch, Reneé ; Tinga, Helma ; van Deurzen, Sander ; Dierick, Maartje ; Hol, Esther ; etc.
Nederlands
boek
Keywords: Maastricht